Nomenclatural studies toward a World List of Diptera genus-group names. Part VI: Daniel William Coquillett - Evenhuis, Neal L. (Zootaxa, 2018)
The Diptera genus-group names of Daniel William Coquillett are reviewed and annotated. A total of 136 available genus-group names in 53 families of Diptera are listed alphabetically, and for each name giving author, year and page of original publication, originally included species, type species and method of fixation, current status of the name, family placement, and a list of any emendations of it that have been found in the literature. Remarks are given to clarify nomenclatural or taxonomic information. In addition, an index to all the species-group names of Diptera proposed by Coquillett (1,218, of which 1,214 are available names) is given with bibliographic reference (year and page) to each original citation. Appended to this study is a full bibliography of Coquillett’s published works.      Name found to be unavailable: Philhelius Coquillett, 1910.      Name found not to be preoccupied: Petia Coquillett, 1910 [Tachinidae].      Corrections to and clarifications of type species designations are made for the following: Isostomyia Coquillett, 1906 [Culicidae]; Micraedes Coquillett, 1906 [Culicidae]; Roederiodes Coquillett, 1901 [Empididae]; Stilbometopa Coquillett, 1899 [Hippoboscidae]; Tinolestes Coquillett, 1906 [Culicidae].      Previous First Reviser actions for multiple original spellings missed by previous workers include: Ateloglossa Coquillett, 1899 [Tachinidae]; Boreodromia Coquillett, 1903 [Brachystomatidae]; Mythicomyia Coquillett, 1893 [Mythicomyiidae].      The following are new synonymies of their respective senior synonyms: Acemyia Coquillett, 1897b under Acemya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Clytiomyia Coquillett, 1897b under Clytiomya Rondani, 1861, n. syn. [Tachinidae]; Linnaemyia Coquillett, 1897b under Linnaemya Robineau-Desvoidy, 1830, n. syn. [Tachinidae]; Xanthogramma Schiner, 1860 under Philhelius Stephens, 1841, n. syn. [Syrphidae].      Using Reversal of Precedence (ICZN Code Art. 23.9), Scriptotricha Cockerell, 1889 [Tephritidae] is declared a nomen oblitum and Paracantha Coquillett, 1899f [Tephritidae] is declared a nomen protectum.